The debt tax shield in general equilibrium - Fischer, Marcel; Jensen, Bjarne Astrup (Journal of Banking & Finance, 2019)
We study the general-equilibrium effects of the corporate debt tax shield in an endowment economy with a redistributive tax system that taxes firm profits and household income and redistributes tax revenues in an attempt to harmonize households’ lifetime consumption opportunities. In general equilibrium, the debt tax shield not only affects corporate capital structure and valuation but also causes poorer households to consume more and save less at a younger age. Without the debt tax shield, the same welfare improvements for poorer households are achievable with significantly lower tax rates.